2015
DOI: 10.1080/00927872.2014.939273
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Properties of the Hawaiian Earring Group for HNN Extensions

Abstract: In 2011, while investigating fundamental groups of wild spaces, K.Eda [7] showed that the fundamental group of the Hawaiian earring (the Hawaiian earring group, in short) has the property that for any homomorphism h from it to a free product A * B, there exists a natural number N such that is contained in a conjugate subgroup to A or B. In the present article, we prove a corresponding property for certain HNN extensions and amalgamated free products. This allows us to show that some one-relator groups, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Free (abelian) groups were classically shown to be cm-slender, lcH-slender and n-slender (see [23] and [34]). More recent work has shown that torsion-free word hyperbolic groups, right-angled Artin groups, braid groups and many other groups satisfy various of these slenderness conditions (see [17,20,39,44]). Note that a group which is either n-slender, cm-slender, or lccH-slender must be torsion-free.…”
Section: Problem 1 Does There Exist a Finitely Generated (Countable) Torsion-free Acylindrically Hyperbolic Group Which Does Not Admit Unmentioning
confidence: 99%
See 1 more Smart Citation
“…Free (abelian) groups were classically shown to be cm-slender, lcH-slender and n-slender (see [23] and [34]). More recent work has shown that torsion-free word hyperbolic groups, right-angled Artin groups, braid groups and many other groups satisfy various of these slenderness conditions (see [17,20,39,44]). Note that a group which is either n-slender, cm-slender, or lccH-slender must be torsion-free.…”
Section: Problem 1 Does There Exist a Finitely Generated (Countable) Torsion-free Acylindrically Hyperbolic Group Which Does Not Admit Unmentioning
confidence: 99%
“…Results like Theorems A and B are called atomic properties in the literature (see [25] and [44]). Note that in Theorems A and B we are not requiring the group G to be acylindrically hyperbolic.…”
Section: Introductionmentioning
confidence: 99%